Lithium - A general overview of its uses - Vermeulen, Raymond A (My University, 1985)
This dissertation consists of a review of the literature, past and present, pertaining to the metal lithium. An overview is presented of its actions, its adverse effects, and its use in medicine particularly in psychiatry. As it is not irregular for many patients to receive two or more drugs concomitantly and often in a combination which has the potential to interact adversely, an overview of these interactions is also presented.
A dissertation submitted to the Faculty of Medicine in part fulfilment of the requirements for the Degree of Master of Medicine in Psychiatry at the University of the Witwatersrand. Johannesburg
Keywords: Lithium; Pharmacokinetics; Pharmacology; Diuretics; Bipolar Disorder